GAMBARAN PEMAKAIAN KB SUNTIK BERDASARKAN TINGKAT PENGETAHUAN IBU TENTANG ALAT KONTRASEPSI DI KELURAHAN PEGAGAN LOR ,KAB.CIREBON TAHUN 2020 - Musfiroh, Sri (MIDWIFERY JOURNAL, 2021)
Background: Regulation Law No.52 of 2009 concerning the development of education and family development states that family development is an effort to create quality families who live in a healthy environment; and family planning is an effort to regulate the birth of children, the ideal distance and age to give birth, to regulate pregnancy, through promotion, protection, and assistance in accordance with reproductive rights to create a quality family. This law supports the family planning program as one of the efforts to create a healthy and quality family. The regulation of pregnancy in the family planning program is carried out using contraception.Objective: To find out the description of the use of injectable contraception based on the mother's level of knowledge about contraceptive devices in Pegagan Lor Kab. Cirebon Year 2020Methods: The variables in this study were knowledge and types of injecting family planning use, the subjects were mothers who used injectable family planning in Pegagan Lor Village on December 14, 2020-10 January 2021, the instrument used was a questionnaire, and the research method was descriptive with a cross sectional approach.Results: The results of the analysis of the total research score of 43.4% of respondents' knowledge included in the less category, and as many as 83% used 3-month injectable contraception.Conclusion: The majority of respondents lack knowledge, and the majority of respondents use 3-month injectable contraception.Suggestion: Midwives are expected to improve health services, especially in providing counseling about injectable contraception devices clearly so that acceptors know about the uses, side effects and advantages of injectable contraception. And it is hoped that this research can be used as a comparison for further research by taking different samples, variables and methods. Keywords: Knowledge, injectable family planning  ABSTRAKLatar Belakang: Undang-undang nomor 52 tahun 2009 tentang perkembangan pendidikan dan pembangunan keluarga menyatakan bahwa pembangunan keluarga adalah upaya mewujudkan keluarga berkualitas yang hidup dalam lingkungan yang sehat; dan keluarga berencana adalah upaya mengatur kelahiran anak, jarak dan usia ideal melahirkan, mengatur kehamilan, melalui promosi, perlindungan, dan bantuan sesuai hak reproduksi untuk mewujudkan keluarga berkualitas. UU ini mendukung program KB sebagai salah satu upaya untuk mewujudkan keluarga sehat dan berkualitas.Pengaturan kehamilan dalam program KB dilakukan dengan menggunakan alat kontrasepsi.Tujuan: Untuk Mengetahui Gambaran Pemakaian KB suntik berdasarkan  Tingkat Pengetahuan Ibu Tentang Alat Kontrasepsi  di Kelurahan Pegagan LorKab. Cirebon Tahun 2020Metode:  Variabel dalam Penelitian ini adalah Pengetahuan dan jenis pemakaian KB Suntik, subjeknya adalah ibu yang menggunakan KB suntik di Kelurahan Pegagan Lor pada tanggal 14 Desember 2020-10 januari 2021, intrumen yang digunakan adalah quesioner, dan metode penelitian menggunakan deskriptif dengan pendekatan cross secsionalHasil: Hasil analisis dari total skor penelitian pengetahuan responden 43,4 % termasuk kedalam kategori kurang, dan  dan sebanyak 83 % menggunakan KB suntik 3 bulan.Kesimpulan: Mayoritas pengetahuan responden kurang, dan mayoritas responden menggunakan KB suntik 3 bulan.Saran: Diharapkan Bidan meningkatkan pelayanan kesehatan khusunya dalam memberikan konseling tentang alat kontrasepsi KB suntik secara jelas agar akseptor mengetahui tentang kegunaan ,efek samping   dan kelebihan KB Suntik. Dan Diharapkan penelitian ini dapat dijadikan bahan pembanding  penelitian selanjutnya dengan mengambil sampel,variable dan metode yang berbeda.